Design and performance analysis on a new electro-hydraulic hybrid transmission system. (2017) - Yang, Yang; Luo, Chang; Li, Pengxi
To avoid the impact of large charge and discharge current on the cycle life of the battery in the process of driving or braking of pure electric vehicle, a new electro-hydraulic hybrid power transmission system was designed. Taking the ChangAn prototype as a reference, a method based on driving cyclic condition was used to match parameters and develop a novel control strategy. The model of this new electro-hydraulic system and the dynamic model of whole vehicle were established. The cosimulation results verified the effectiveness of the new hybrid power transmission system and the parameter matching method. The results show that the new electro-hydraulic hybrid power transmission system effectively avoids the impact of large charging and discharging current on the battery cycle life, and can improve the economy of vehicles to a significant extent while also displaying satisfactory power performance.